2019
DOI: 10.1038/s41598-019-51255-0
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormone-related polymorphisms associate with the development of bone erosions in rheumatoid arthritis and help to predict disease progression: Results from the REPAIR consortium

Abstract: Here, we assessed whether 41 SNPs within steroid hormone genes associated with erosive disease. The most relevant finding was the rheumatoid factor (RF)-specific effect of the CYP1B1, CYP2C9, ESR2, FcγR3A, and SHBG SNPs to modulate the risk of bone erosions (P = 0.004, 0.0007, 0.0002, 0.013 and 0.015) that was confirmed through meta-analysis of our data with those from the DREAM registry (P = 0.000081, 0.0022, 0.00074, 0.0067 and 0.0087, respectively). Mechanistically, we also found a gender-specific correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…On the other hand, steroid hormone biosynthesis (Cutolo et al, 2004) and p53 signaling were decreased in RA. Steroid hormone-related gene polymorphisms have been linked to bone erosion in rheumatoid arthritis (Sánchez-Maldonado et al, 2019). The p53 signaling pathway mediates the cellular response to stress, cell cycle, DNA repair, senescence, and apoptosis (Hou et al, 2016;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, steroid hormone biosynthesis (Cutolo et al, 2004) and p53 signaling were decreased in RA. Steroid hormone-related gene polymorphisms have been linked to bone erosion in rheumatoid arthritis (Sánchez-Maldonado et al, 2019). The p53 signaling pathway mediates the cellular response to stress, cell cycle, DNA repair, senescence, and apoptosis (Hou et al, 2016;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Study participants were of European origin and gave their written informed consent to participate in the study, which was approved by the ethical review committee of participant institutions: Virgen de las Nieves University Hospital (2012/89); Santa Maria Hospital-CHLN (CE 877/121.2012); University Clinical Hospital of Santiago de Compostela (2013/156); Wroclaw Medical University (KB-625/2016); Radboud university medical center (2011/299) and by the Regional Ethics Committee of Central Denmark Region (S-20120113). A detailed description of the discovery population has been reported elsewhere ( 19 , 20 , 22 , 24 ). All RA patients were naïve for TNFi and response to TNFi for each patient in all study populations was calculated using the change in disease activity score (DAS28CRP) between baseline and 6 months after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Given the high cost of these drugs and the potential impairment of non-responding patients, the identification of genetic biomarkers associated with drug response to specific biological agents would help to know which patients might benefit from a particular treatment. However, to date, only a few genome-wide association studies (GWAS) (11)(12)(13)(14)(15)(16)(17) or well powered candidate gene association studies have been conducted (18)(19)(20)(21)(22)(23)(24)(25)(26). We are far from being able to optimize drug dosing or prioritize drug combinations based on genetic findings.…”
Section: Introductionmentioning
confidence: 99%
“…Of note to TED, these authors noted that a potential background for their findings may have been the down-regulated activity in the growth hormone/IGF-1 axis in males lacking ERa (46). Sańchez-Maldonado, et al, found that 3 ESR1 haplotypes had a reduced risk of erosive arthritis, and that both ESR1 and ESR2 influence the disease (47). Finally, in a colitis mouse model, ERa deletion in T cells reduced their pathogenic potential via increased expression of Foxp3 (42).…”
Section: Estrogen Receptorsmentioning
confidence: 99%